Upaya Meningkatkan Kemampuan Motorik Halus Anak Dengan Kegiatan Mewarnai Gambar Melalui Metode Pemberian Tugas Pada Anak Kelompok B TK Mandiri Serai Wangi Peranap Tahun Ajaran 2022/2023 - Endang Sulastri; Eri Yanti; Darmanina Lisanti (LPPI Yayasan Almahmudi bin Dahlan, 2023)
Children's fine motor skills have not shown good results, in performing fine motor movements, children also need the support of other physical skills and mental maturity. Picture coloring activities at Serai Wangi independent kindergarten are still lacking. When the activity of coloring pictures is carried out there are still many children who play with their friends rather than completing the task. The media provided by the teacher is too large causing children to get bored. The media provided by the teacher is also less varied. The time limit given by the teacher is not appropriate, so that children lack responsibility for image coloring activities. The way the teacher conveys how to color the picture is less precise. Some children still color the picture in two directions. In fact, there are still children who color pictures out of the predetermined pattern lines and are very monotonous. And there are more children who color pictures with only one color. Coloring pictures usually uses crayon media. The focus in this study was group B children of Mandiri Serai Wangi Kindergarten with a total of 10 children consisting of 6 girls and 4 boys. This study uses classroom action research with coloring pictures through the assignment method which is carried out through four stages, namely: planning, action, observation and reflection. This research was conducted in two cycles and each cycle consisted of two meetings. Based on the results of the analysis in cycle I meeting 1 children who were predicated Developing very well only 20% increased in the second meeting to 30%. In cycle II, the first meeting of children who were predicated on developing very well from 30% increased in the second meeting to 60%. The occurrence of an increase from cycle I and silkus II can be concluded that there is an increase with the activity of coloring pictures through the method of giving assignments to children in group B of Mandiri Serai Wangi Kindergarten Peranap Academic Year 2022/2023. Keywords: Fine motor skills, coloring pictures, assignment method